2023
DOI: 10.3389/fpain.2023.1154597
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms and management of persistent postsurgical pain

Abstract: An estimated 10%–50% of patients undergoing a surgical intervention will develop persistent postsurgical pain (PPP) lasting more than 3 months despite adequate acute pain management and the availability of minimally invasive procedures. The link between early and late pain outcomes for surgical procedures remains unclear—some patients improve while others develop persistent pain. The elective nature of a surgical procedure offers a unique opportunity for prophylactic or early intervention to prevent the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 230 publications
0
3
0
Order By: Relevance
“…One possible mechanism of rebound is that regional anesthetics can suppress inflammatory factors and cytokines which are related to activating nociceptor, and degradation of regional anesthetics induces burst of the factors. 25 Dexamethasone, a corticosteroid hormone, has been considered to prolong the analgesia duration of peripheral nerve block and reduce incidence of rebound pain. 8 , 9 , 21 Besides, absence of dexamethasone was reported to be a risk factor of rebound pain.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism of rebound is that regional anesthetics can suppress inflammatory factors and cytokines which are related to activating nociceptor, and degradation of regional anesthetics induces burst of the factors. 25 Dexamethasone, a corticosteroid hormone, has been considered to prolong the analgesia duration of peripheral nerve block and reduce incidence of rebound pain. 8 , 9 , 21 Besides, absence of dexamethasone was reported to be a risk factor of rebound pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided compelling comparative data, shedding light on the tangible benefits of implementing innovative therapeutic interventions. For instance, in a retrospective cohort study by Fuller et al (2023), patients undergoing a novel minimally invasive procedure exhibited a 20% reduction in postoperative pain scores compared to traditional surgical methods. This highlights the new approach's efficacy and underscores its potential to enhance the patient experience (Fuller et al, 2023).…”
Section: Impact Of Therapeutic Approachesmentioning
confidence: 99%
“…For instance, in a retrospective cohort study by Fuller et al (2023), patients undergoing a novel minimally invasive procedure exhibited a 20% reduction in postoperative pain scores compared to traditional surgical methods. This highlights the new approach's efficacy and underscores its potential to enhance the patient experience (Fuller et al, 2023). Furthermore, a comparative analysis of joint replacement surgeries, as outlined in the work of Castrodad et al (2019), revealed a notable decrease in recovery times following the adoption of advanced rehabilitation protocols.…”
Section: Impact Of Therapeutic Approachesmentioning
confidence: 99%
“…5,19 This pain is poorly managed 5 due to a limited understanding of the underlying mechanisms. 13,18 This can lead to persistent postsurgical pain following routine procedures 16,28 and a risk of opioid misuse. 8 A common yet disturbing symptom is "dynamic allodynia," when tactile stimuli such as clothing close to the surgical site elicits pain sensation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Study of this and subsequent related preclinical surgical models provides evidence for both inflammatory and neuropathic components with the involvement of peripheral sensitisation, central neural plasticity, and neuroimmune interactions. 13,18,28 Behavioural readouts from multiple studies report thermal hyperalgesia and punctate Sponsorships or competing interests that may be relevant to content are disclosed at the end of this article. mechanical hypersensitivity (reviewed).…”
Section: Introductionmentioning
confidence: 99%